Cervical chondrocutaneous branchial remnants: A report of 29 cases and review of the literature. Issue 2 (April 2021) - Ishigaki, Tatsuya; Akita, Shinsuke; Suzuki, Hiroyuki; Udagawa, Akikazu; Mitsukawa, Nobuyuki
Abstract: Objective: Cervical chondrocutaneous branchial remnants (CCBRs) are rare masses located in the anterior region of the neck. Though the basic characteristics of these rare masses were first described by Atlan in 1997, a critical amount of information about these masses remains unknown. This study aimed to further clarify the characteristics of these rare masses. Methods: We retrospectively reviewed the clinical records of patients with CCBRs in our facility during a 32-year period ranging from 1988 to 2019. We then compared our clinical records with other case reports. Results: There were 29 patients with CCBRs in our facility, including 19 males and ten females, Three patients were involved bilaterally (among patients involved unilaterally, the right side included 11 patients, and the left side was 15 patients), eight patients also had associated abnormalities. We submitted CCBRs from 18 patients to pathology, and all of them contained elastic cartilages. Among all the surgical data could be confirmed, cartilages did not reach beyond the musculature of the neck. We could confirm a similar tendency with Atlan regarding sex, the location of CCBRs (involvement side, localization in the neck), and the depth of CCBRs. Among the cases contained in this study, there was a disparity in the rate of associated abnormalities and pathology of contained cartilages. Conclusion: Some critical characteristics of CCBRs included, a male predominance, scarcity of bilateral cases and common left side involvement among unilateral involved cases, a common location of CCBRs in the inferior third of the neck and anterior to the sternocleidomastoid muscle, and an involvement of cartilage in CCBRs which has no connections to deep underlying structure of the neck. Further investigations are required to determine the origin of CCBRs and the precise incidence of the associated abnormalities. Systemic examination in patients with CCBRs is recommended because many associated abnormalities have been reported.